Assessing balance in an athletic population: normative data for the concussion balance test (COBALT©) - Massingale, S. L.; Alexander, A. D.; Erickson, S. M.; McQueary, E. S.; Gerkin, R. D.; Schodrof, S. B.; Kisana, H. M.; Pardini, J. E. (International Journal of Athletic Therapy & Training, 2018)
Dizziness and balance problems are commonly reported symptoms following sport-related concussion. The Concussion Balance Test (COBALT©), is an eight-condition test that assesses postural control with active vestibular stimulation using force plate technology. The purpose of this study was to establish normative data on COBALT for athletes ages 10-18. Data for postural sway velocity and error rates were acquired in 514 athletes presenting for preparticipation baseline screening. Six test conditions showed little variation in sway and error rate; however, two challenging conditions showed significant variation in sway among youth athletes.